Superabsorbent derived from cassava waste pulp - Zainal Alim Masâud; Mohammad Khotib; Muhamad Farid; Anwar Nur; Muhamad Amroni (International Journal of Recycling of Organic Waste in Agriculture)
Background: Cassava waste pulp from the tapioca industry is abundant in Indonesia. However, there have been few Indonesian or international papers describing research on the possible use of cassava waste pulp as a superabsorbent after modification. The goal of this work was to increase the added value of cassava waste pulp by converting it into a superabsorbent. This conversion was carried out by a graft copolymerization of cassava waste pulp using acrylamide, ammonium persulfate, and N,Nâ²-methylene-bisacrylamide as a monomer, an initiator, and a crosslinker, respectively. The copolymerization was conducted at 70°C for 3 h and saponified with 1 M NaOH for 2 h. Results: The superabsorbent had a maximum water absorption capacity of 1,014 g/g at pH 7.3; the absorbency was affected by the salinity of the medium. The rate parameter for absorption in distilled water was 5.4 min. The formation of a superabsorbent was confirmed by FTIR spectroscopy, as the spectra exhibited all characteristic bands of both cassava waste pulp and acrylamide. Conclusion: Cassava waste pulp has a great potential to be used as a superabsorbent, which could give added value to cassava